National Trends in Pulmonary Embolism Visit in United State Emergency Departments and Associated Costs (2006–2018) - Ahmad Aalam; Diyaa Bokhary; Awad Alsabban; Ahmad Bakhribah (Emergency Medicine International)
Conclusion: From 2006 to 2018, PE ED visits in the US increased with a noticeable decrease in admission rates and length of stay, likely secondary to advancement in diagnostic and therapeutic modalities like computed tomography pulmonary angiography and novel oral anticoagulants. However, the observed rising healthcare costs pose challenges to sustainable management. Further research studies are needed to address cost-effective strategies.